Enhancing organic product purchases: A study on environmental and novelty consciousness, trust, and the mediating role of word-of-mouth among organic sea salted fish consumers in Maumere, Sikka Regency-Indonesia - Majid, Abdul; Kusmaningtyas, Amiartuti; Cempena, Ida Bagus (Edelweiss Applied Science and Technology, 2024)
This study examines the influence of environmental consciousness, novelty consciousness, and trust in organic products on actual purchase behavior, mediated by word-of-mouth, among organic salted fish consumers in Maumere, Sikka Regency. Organic salted fish, produced without synthetic chemicals, offers a healthier and environmentally friendly alternative for health-conscious and environmentally aware consumers. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), data will be collected from 100 purposively sampled respondents through a questionnaire measuring relevant variables. The findings reveal that word-of-mouth significantly mediates the relationships between environmental consciousness, novelty consciousness, trust in organic products, and actual purchase behavior, providing valuable insights into consumer behavior dynamics and supporting sustainable consumption in the local market.